Assessment of the Quality of Life of Healthcare Workers in Nigeria during COVID- 19 Pandemic - Imishue, Onome Tobore; Ogunkoya, John Omotola; Jagun, Omodele; Ladele, Akindele Emmanuel; Betiku, Anthony (European Journal of Applied Sciences, 2023)
Background: COVID-19 pandemic caused increased pressure at work, coupled with a lack of appropriate infection prevention and treatment guidelines, and led increased work burdens, increased burnout, psychological symptoms, and post-traumatic stress. The quality of life of healthcare workers during the pandemic can therefore have a profound negative impact on the healthcare needs of the general population. Aims/objectives: This study was designed to explore the mental health status among HCWs in Nigeria during the first wave of Covid-19 pandemic and identify the determining factors. Methods: A cross-sectional study carried out using a semi-structured online questionnaire. SurveyMonkey was used as the survey platform. The questionnaire used was distributed through email and WhatsApp. The study participants were HCWs in Nigeria and were recruited using a non-probability purposive sampling technique. Results: Responses gotten from one hundred and fifty-four (154) participants were included in this study which was made up of 84(54.5%) females and 70(45.5%) male participants. The mean age of respondents was 38.8±8.1 years. More than half of the respondents were doctors (50.6%, n=78), followed by Nurses (33.1%, n=51). The mean composite SOS-10 score was 51.6±7.63. Majority of study participants recorded good composite score (94.2%, n=145) with only one participant having a poor score (0.6%). The median composite SOS-10 score of respondents was 52 (of a maximum of 60), with an interquartile range of 49-47. There was no correlation between the respondent’s age, sex, religion, marital status, professional status, medical history, medical insurance, and the number of years and SOS-10 scores (rs = 1.00, p >0.05). However, there is a correlation between the respondents’ general health rating and SOS-10 scores (p=0.001). Conclusion: This study found that the QoL of healthcare workers in Nigeria was not affected by the COVID-19 pandemic during the first wave of the pandemic